Sports magazines in the system of scholarly communication - Svistel'nik, I.R. (Pedagogics, psychology, medical-biological problems of physical training and sports, 2013)
The paper presents the sports scientific journals that form the system of documentary research information. We describe the formation, development and progress of scientific publications and their typological features of forming and problem-oriented content. Outlined sufficiency specialized sports magazines. Analysis of scientific publications in Ukraine, Russia, Belarus, presented their names and entry into the national and international abstracting. Posted sports for scientific publications USA, UK, China, Poland and many other countries that carry information for sports, sports training, medical and biological problems of physical education. It is shown that most of the study sports science publications printed in the United States, slightly less than in the UK, Poland and Germany. Determined that scientific journals help speed the spread of sports information, disseminate the results of modern research.